Afrikanermynwerkers en die Mynwerkersunie, 1936-1948 (Historia, 2021)
Between the years of 1936 and 1948 a bitter struggle waged in the ranks of the white Mine Workers Union (MWU) for control of this large and influential organisation. In essence it was a struggle of the unskilled and semi-skilled Afrikaner mine workers against the gross maladministration of the Union management. This struggle was, however, organised and fanned from the outside by Afrikaner political and cultural leaders ("Die Nasionale Raad van Trustees" or NRT) in an attempt to mobilise the Afrikaner workers for party political and Afrikaner national interests. Their vehicle was the "Afrikanerbond van Mynwerkers" (ABM) -which, as an opposing christian national union, tried to oust the MWU. The first serious attempt was warded off by reinstating the closed shop principle and thus making a second union illegal. Thereafter the ABM tried to reform the MWU from within and during a lengthy struggle succeeded in bringing the maladministration of the MWU in the open. In 1947 the struggle was won when a new Afrikaner dominated board of management was elected. The article focuses on the role of the NRT and ABM and the ways in which it mobilised support from Afrikaners, the majority of whom did not have the same strong feelings of nationhood as the leaders of the ABM/NRT. In evaluating the role of the ABM/NRT the evidence indicates that in the initial phase of the struggle it played an important role, but in the latter stages it was partially pushed into the background by groups of mine workers committed to the basic principles of trade unionism and not in the first instance to Afrikaner solidarity.Tussen 1936 en 1948 het daar 'n bittere stryd in die geledere van die Mynwerkersunie (MWU), die Blanke mynwerkersvakbond aan die Witwatersrand, geheers. In die middelpunt van die stryd was die Afrikanermynwerkers wat nie alleen die oorgrotemeerderheid van die Blanke mynwerkers verteenwoordig het nie, maar wat as ongeskooldes en semi-geskooldes van die laagste lone in die mynbedryf ontvang het. Die stryd van die mynwerkers was enersyds gemik teen die bestuur van die MWU a.g. v. wanadministrasie, magsmisbruik en gebrekkige behartiging van die belange van die mynwerkers. Andersyds was daar kragte van buite die geledere van die MWU wat die Afrikanermynwerker probeer mobiliseer het vir kultureel-politieke doeleindes: Afrikanereenheid en -mag. Die stryd van die mynwerkers was nie beperk tot die arena van die georganiseerde arbeid nie, maar dit het ook 'n brandpunt in die politieke lewe van daardie jare geword. Die botsende belange van die mynbase en mynwerkers is in 'n belangrike mate weerspieël in die stryd tussen die Verenigde Party (VP), die Arbeidersparty (AP) en die "Gesuiwerde" Nasionale Party (GNP). Histories gesien was hierdie stryd van groot belang, want dit het aan die wortels gelê van 'n sterk opkomende Afrikanernasionalisme.
Keywords: History; Geskiedenis; Afrikanerbond of Mine workers; Mynwerkersunie; Nasionale Raad van Trustees; Industrial relations; Mine Workers' Union; Blanke Mynwerkersvakbond; Historia; 1936-1948